Efektivitas Pelaksanaan Pelayanan Pengaduan Masyarakat Berbasis E-Government - Mahendra, Gerry Katon; Pribadi, Ulung (Journal of Governance and Public Policy, 2014)
Public complaints service today’s has become part of  the efforts to improve public services in Indonesia. Government,both central and local levels is appropriate to give special attention to the improvement of  service quality of  publiccomplaints. The government’s attention can be achieved either by continuously innovate to create public complaintsservice that is not only easily accessible by the public, but  also can be received and responded  to effectively by localgovernment. Yogyakarta City’s Government innovates by providing the services of  public complaints were based oninformation technology and communication (e-government). Innovations made by the government of  Yogyakar ta isexpected to provide ease of  access for the public and can be input which should be followed up effectively by thegovernment of  the city of  Yogyakarta so as to create improved quality of  public services in general in the future.